2021
DOI: 10.3389/fphar.2021.759157
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Strategy From In Vitro, In Situ, In Vivo to In Silico for Predicting Active Constituents and Exploring Molecular Mechanisms of Tongfengding Capsule for Treating Gout by Inhibiting Inflammatory Responses

Abstract: The study of screening active constituents from traditional Chinese medicine (TCM) is important for explicating the mechanism of action of TCM and further evaluating the safety and efficacy effectively. However, detecting and identifying the active constituents from complicated biological samples still remain a challenge. Here, a practical, quick, and novel integrated strategy from in vitro, in situ, in vivo to in silico for rapidly screening the active constituents was developed. Firstly, the chemical profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Tongfengding capsule has been shown in studies to have an anti-gouty arthritis effect by inhibiting the secretion of the inflammatory factors TNF-α and IL-6. Furthermore, its mechanism may be linked to the inhibition of the arachidonic acid signaling pathway [151]. Xiaofeng granule is made from a new formula that has been improved from modified simiaowan and has heatclearing and dampness-drying properties.…”
Section: Tcm Prescription For Goutmentioning
confidence: 99%
“…Tongfengding capsule has been shown in studies to have an anti-gouty arthritis effect by inhibiting the secretion of the inflammatory factors TNF-α and IL-6. Furthermore, its mechanism may be linked to the inhibition of the arachidonic acid signaling pathway [151]. Xiaofeng granule is made from a new formula that has been improved from modified simiaowan and has heatclearing and dampness-drying properties.…”
Section: Tcm Prescription For Goutmentioning
confidence: 99%
“…Based on different preparation methods, the 2020 Chinese Pharmacopoeia calculates the content of total anthraquinone and free anthraquinone (above 1.5 and 0.02%, respectively) as to control the quality of rhubarb, in terms of the total amount of aloe-emodin, rhein, emodin, chrysophanol, and physcion. It is generally believed that substances that produce curative effects are TCM prototype components or their metabolites, which enter systemic circulation to reach the target organs ( Li et al, 2018 ; Zhou et al, 2020 ; Zhu et al, 2020 ; Yang et al, 2021 ). Although anthraquinones show good pharmacological activities in vitro , including laxative, anticancer, hepatoprotective, anti-inflammatory, antibacterial, analgesic, and other effects ( Xiang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can clear away heat and dampness, promote blood circulation, dredge collaterals, and calm pain, which is mainly used for treating gout. The study found that TFDC might inhibit the inflammatory response in treating gout by regulating the arachidonic acid metabolic pathway, especially its active compound apigenin could significantly inhibit the related targets of prostaglandin G/H synthase 2 (PTGS2), tumor necrosis factor- α (TNF- α ), and interleukin-6 (IL-6) in this pathway [ 9 ]. Clinically, TFDC could improve blood uric acid levels in patients and reduce adverse reactions such as stomach discomfort and mild diarrhea, so as to better treat GA [ 10 ].…”
Section: Introductionmentioning
confidence: 99%